Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1637/11789-122717-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose Concentrations in Nicarbazin-Fed Broiler Chickens

Abstract: Four floor pen studies were carried out to evaluate the effects of nicarbazin (NIC) administration on blood glucose concentrations and the onset of hypoglycemia in broiler chickens. All tests involved continuous NIC feeding at 0, 100, or 125 ppm to 28 days of age. In each study, birds were reared at both standard environmental temperatures and at 3 C below this level. In addition, two studies were conducted in the presence of coccidial infection and two were carried out in noninfected broilers. At 26 days of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There is no clear explanation for the increased feed intake in the PC and FP group, but we can speculate that the nutrient digestion and absorption in the PC group is severely impaired due to coccidial challenge compared with the FP group. It has been reported that the blood glucose levels of broilers under coccidial challenge are decreased, and blood glucose levels are negatively associated with appetite [ 45 , 46 ]. Thus, the blood level in the PC group is supposedly lower due to the low efficiency of nutrient absorption, thereby stimulating appetite in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…There is no clear explanation for the increased feed intake in the PC and FP group, but we can speculate that the nutrient digestion and absorption in the PC group is severely impaired due to coccidial challenge compared with the FP group. It has been reported that the blood glucose levels of broilers under coccidial challenge are decreased, and blood glucose levels are negatively associated with appetite [ 45 , 46 ]. Thus, the blood level in the PC group is supposedly lower due to the low efficiency of nutrient absorption, thereby stimulating appetite in the hypothalamus.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on blood glucose in avian, measurements were made using whole blood. However, it is difficult to find consistency from blood collection techniques to measurement methods and results [22][23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Even fasting blood sugar levels are less likely to change 26 . In the literature, there are differences in blood glucose analysis studies performed in chick embryos and newly hatched chickens 23,24 . In addition, there are differences between techniques in terms of mean blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose concentration is often used as a biological evaluation index in studies that evaluate the effects of dietary components on rearing conditions and health abnormalities. Moreover, in research involving blood glucose, measurements have been performed using whole blood ( Burns et al , 2002 ; Bafundo et al , 2018 ), plasma ( Smith and Baranowski-Kish, 1976 ), or serum ( Brake et al , 1981 ; Daly and Peterson, 1990 ; Latour et al ., 1996 ; Peebles et al ., 2012 ; Sahin et al ., 2018 ), and it is difficult to find consistency from blood collection techniques to measurement methods and results. Glucose is the main carbohydrate in circulation in birds and its concentration is controlled by pancreatic hormones, glucagon, and insulin ( Scanes, 2015 ).…”
Section: Introductionmentioning
confidence: 99%